Organizing and participating in meetings - Leigh, Judith (Oxford University Press, 2002)
This lively and accessible guide will enable you to approach meetings positively by taking you through each stage from initial invitation through to reading the final minutes. In two sections, it gives step-by-step guidance on what happens at both formal and informal meetings and how to participate productively. Topics include telephone meetings, online meetings, and video conferencing, creating agendas, writing papers or reports, chairing meetings, and presenting a paper. This guide is not only aimed at those attending or organizing business meetings, but also at those attending meetings in non-work scenarios such as societies, voluntary organizations, charities, and local groups